Associations among disability, depression, anxiety, stress, and quality of life between stroke survivors and their family caregivers: An Actor‐Partner Interdependence Model. (18th October 2022) - Yuliana, Sri; Yu, Erica; Rias, Yohanes Andy; Atikah, Nur; Chang, Hsiu Ju; Tsai, Hsiu Ting
Abstract: Aim: To explore the effects of disability, depressive, anxiety and stress symptoms on patients' and their partners' quality of life (QoL) using the actor–partner interdependence model (APIM). Design: A cross‐sectional study using actor–partner interdependence model. Methods: We recruited 183 dyads of stroke survivors and their family caregivers in Indonesia. The World Health Organization Disability Assessment (WHODAS 2.0), Depression, Anxiety and Stress (DASS‐42) and Rand Short Form Health Survey (SF‐36) were used to measure disability, depressive, anxiety and stress symptoms and QoL of stroke survivors and family caregivers. The actor–partner interdependence model was tested using multilevel modelling. The actor–partner interdependence mediation model (APIMeM) was applied to estimate the direct and indirect effect. Results: Disability had actor effects on stroke survivor's overall QoL and partner effect on family caregiver's overall QoL. More severe disability of stroke survivors was associated with a lower overall QoL of their own and that of family caregiver's overall QoL. Depressive symptoms of stroke survivors had actor effects on stroke survivors' overall QoL and partner effects on family caregivers' overall QoL. Actor and partner effects also exist on family caregiver's depression symptoms to their own overall QoL and stroke survivor's overall QoL. Moreover, higher anxiety symptoms were associated with lower levels of their own and partner's overall QoL in both stroke survivors and family caregivers. Stroke survivor's stress symptoms also negatively associated with their own and family caregiver's overall QoL. However, a family caregiver's stress without a partner effects on stroke survivor's overall QoL. The APIMeM analysis showed that disability of stroke survivors directly decreased their own overall, physical (PCS) and mental QoL (MCS). Also, disability mediated by stroke survivor's depression, anxiety and stress symptoms decreased both stroke survivor's and family caregiver's physical (PCS) and mental QoL (MCS). Conclusion: The findings suggest that stroke survivors and family caregivers may influence each other during the caregiving process and social life. The disability of stroke survivors, and the depression, anxiety and stress symptoms of stroke survivors and family caregivers affect their own QoL and their partners' QoL. Disability of stroke survivors directly decreased their own overall, physical (PCS) and mental QoL (MCS). Also, it indirectly via stroke survivor's depression, anxiety and stress symptoms decreased both stroke survivor's and family caregiver's physical (PCS) and mental QoL (MCS). Impact: Dyadic actor–partner interdependence models have shown promising potential to predict the QoL among patients and family caregivers. The dyadic effects of disability, depression, anxiety and stress symptoms on the QoL of stroke survivors and family caregivers can be applied to guide the future development of nursing intervention addressed decreasing depression, anxiety and stress symptoms to optimize health outcomes among stroke survivors and their family caregivers.